Assessing the Impact of Management Options on Water Allocation in River Mubuku-Sebwe Sub-Catchments of Lake Edward-George Basin, Western Uganda - Mwebaze, Caroline Ednah; Mwanjalolo Majaliwa, Jackson-Gilbert; Wanyama, Joshua; Gabiri, Geoffrey (Water, 2021)
Limited studies in East Africa and particularly in Uganda have been carried out to determine and map water use and demands. This study aimed at assessing the impact of management options on sustainable water allocation in environmentally sensitive catchments of Mubuku and Sebwe of Lake Edward-George basin in Western Uganda. We used hydro-meteorological data analysis techniques to quantify the available water. We applied Mike Hydro model to allocate water to the different ongoing developments in the catchment based on 2015 and 2040 water demand management scenarios. We used the Nile Basin Decision Support System to assess the sustainability of the different water management scenarios for sustainable water resources use. Reliability computation did not consider hydropower in this study. Results show that water available in 2015 was 60 MCM/YR and 365 MCM/YR for Sebwe and Mubuku, respectively and is projected to decrease by 15% and 11% by the year 2040 under climate scenario RCP8.5. We project water demand to rise by 64% for domestic, 44% for livestock, 400% for industry, 45% for hydro power and 66% for irrigation by 2040. Mubuku water demand is projected to increase from 5.2 MCM in 2015 to 10.7 MCM in 2040. Mubuku available water is projected to fall from 364.8 to 329.8 MCM per annum. Sebwe water demand is projected to increase from 9.7 MCM in 2015 to 22.2 MCM in 2040 and its available water is projected to fall from 60 to 52 MCM per annum by the year 2040 from 2015. Water managers ought to allocate water based on the reliable water allocation which prioritizes domestic and environmental water demands, allocates 90% of industrial demand, 70% of irrigation and 60% of livestock demand. We recommend institutionalizing this model to guide water allocation in the Mubuku-Sebwe sub catchments. Water users should employ more efficient water use techniques to achieve high reliability and sustainable water resources management.
Keywords: Sustainable water allocation; Water balance; River Basin model; Mubuku River; Sebwe River; Rwenzori region